A novel approach to analyze beam-like composite structures using mechanics of structure genome. (October 2016) - Liu, Xin; Yu, Wenbin
Highlights: Euler–Bernoulli beam element and Timoshenko beam element based on the constitutive modeling using mechanics of structure genome. New beam elements implemented in CALCULIX so that complex slender structures can be accurately analyzed using simple engineering beam models. The software is in the cloud freely accessible by anybody through any device connected to Internet. The present work enables engineers to use efficient 1D beam elements to achieve the accuracy of detailed 3D FEA. Abstract: A novel approach to the analysis of beam-like composite structure is introduced in this paper. New software Gmsh4SC is developed based on two well-known open source codes Gmsh and CalculiX. One-dimensional Euler–Bernoulli and Timoshenko type finite elements are derived based on the constitutive models obtained by using Mechanics of Structure Genome (MSG). Gmsh4SC is connected to a general-purpose composites software SwiftComp TM, which implements MSG to carry out the constitutive modeling. The software can be executed in the cloud at https://cdmhub.org/tools/scstandard. Several beam-like composite structures are analyzed by this newly developed software. The accuracy and efficiency of the proposed method are verified by three-dimensional (3D) finite element model using the commercial code ABAQUS.